Osmotic membrane distillation regeneration of liquid desiccant solutions used for air conditioning: a proof of concept - Duong, Hung Cong; Nguyen, Nhan Trong; Doan, Oanh Thi; Tran, Lan Thi Thu (Vietnam Journal of Science and Technology, 2022)
Liquid desiccant air-conditioning (LDAC) has emerged as a promising technology to meet the increasing demand for indoor thermal comfort. In LDAC systems, regeneration of liquid desiccant solution is a critical step. Direct contact membrane distillation (DCMD) has been explored for regeneration of liquid desiccant solutions used in LDAC systems, but faced with the technical challenges caused by the hyper salinity of the solutions. Osmotic membrane distillation (OMD) is a variant of DCMD that can treat hyper saline waters. In this study, a proof of concept of OMD regeneration of liquid desiccant solution was experimentally demonstrated. Compared to DCMD, the OMD process exhibited significantly higher water flux due to the reduced water vapor pressure on the permeate side of the membrane. Indeed, the OMD process of the liquid desiccant LiCl 20% solution feed achieved water flux two-fold higher than that of the DCMD process under the same operating conditions. Given its increased water flux, the OMD process could regenerate the LiCl solution of much higher concentration: the OMD process with the initial CaCl2 20% solution osmotic agent concentrated LiCl solution from 20% to 38.4% after a continuous 8-hour operation.